Nigger ManifestoInstitutional, Intellectual and Ideological Racism inside the American Academy - J. D, Ellis Washington (2023)
For over 30 years I have worked indefatigably, I have labored assiduously to build a relevant resume; as an iconoclastic law scholar zealous for natural law, natural rights, and the original intent of the constitutional Framers–a Black conservative intellectual born in the ghettos of Detroit. Yet as a Black intellectual what is my reward for 30 years of meticulous research? My reward is that in a de jure (legal) and de facto (unofficial) sense I am effectively blacklisted by White and Black Progressive academics who over the past 50 years have increasingly come to dominate the Academy. Instead of being welcomed as an equal, my prolific scholarly output has been mocked, marginalized, slandered, and scrupulously ignored by the academic community. We, conservative scholars, academics, and intellectuals have no home to go to in our futile, Sisyphus- like search for good faith faculty interviews. We are discriminated against, ignored, mocked, summarily rebuffed, and quickly learn that we are faced with the ubiquitous, chilling, yet invisible sign above every faculty inquiry —NO CONSERVATIVES NEED APPLY!